Fair allocation of resources in the moral dilemma of triage - Peer Keßler; Ivar Krumpal (Frontiers in Sociology)
Against the background of the COVID-19 pandemic that has shaken societies around the world, the debate about fairness of medical allocation decisions is gaining momentum. Studying a sample of a broad international public (N = 1,998), we investigate citizens' ethical preferences in the moral dilemma of triage decisions. First, we address the key problem of which of several contradictory ethical criteria and normative principles should be used to determine the fairness of outcomes in triage situations. Preferences about fair outcomes are inferred from observed allocation decisions in a conjoint experiment. Second, preferences in regard to fair procedures are measured via fairness ratings of a series of triage procedures. Third, we analyze the relationship between the observed allocation outcomes and the fairness ratings of procedures. Finally, we review the current expert discourse and reflect it with the citizens ethical preferences observed in our study.